Blackout store / Muhammad Shameerul Akif Abd Halim and Luqman Arif Zulkarnaim - Abd Halim, Muhammad Shameerul Akif; Zulkarnaim, Luqman Arif
Entrepreneurship is the process of designing, launching and running business, which is nore than not, initially a small business, offering a product, process or service for sale or hire. ENT600 is one of the subjects that have to be taken for the students of mechanical engineering on semester 7 that related to the entrepreneurship. Students are required to select on Small and Medium-sized Enterprises (SME)'s company as a reference material and make a case study about the company. We select Blackout Resource and Trading as our reference company. Entrepreneur is defined as an individual who organizes or operates a business. It often conflated with the terms "small business" or used interchangeably with this term. While most entrepreneurial ventures start out as a small business, not all small business are entrepreneurial in the strict sense of the term. Many Small business are sole proprietor operations consisting solely of the owner, or they have a small number of employees and many of these small business offer an existing product, process or service. The major purpose of this case study is to analyze a real-life situation of a business where existing problems need to be solved. We have to relate the theory with practical situation by applying the ideas and knowledge in the coursework to real situation. We are required to identify the problems that they encounter. The major problems will be discussed and the solutions will be gathered. The best solution and it details the will be implemented. The business problems that our case study created to address are about the process involved and technology used. The problems that we identify are mostly about its processes and services that manually operated using manpower. The example is when the staff of the store manually using their hand to clean the customer shoes and its takes time to fully dry.